Tourist’s Attitudes and Perceptions Through The Interest of Traditional Food: Case Study of Kerak Telor Jakarta - Rini, Nuryadina Augus; Karlina, Karlina (Stupa, 2020)
Indonesia is an archipelago with natural wealth and cultural diversity. The tourism sector has become a principal source of income tourism in Jakarta. The tourists who come to Jakarta is expected to not only interested in natural beauty, the unique nature, but also interested in its culinary. Specialty culinary in Jakarta is Kerak Telur (Crust Eggs). The purpose of this research is to find the attitudes and perceptions of tourists in selecting Kerak Telur. These factors can be seen in terms of products, the price, promotion, place, services, process, and suggestions physical. The research was conducted in DKI Jakarta during one year by using quantitative and qualitative methods. The use of quantitative method was the quantitative instruments and a qualitative method was used to describe and explain why tourists select Kerak Telur (Crust Eggs) in Jakarta detail. From this research result, it was known that some factors influencing the tourist in interest in buying Kerak Telur (Crust Egg) partially were the location, the process, and people, but simultaneously the products, the price, the promotion, the location, the process, physical means, and people have a great influence to buy Kerak Telur (Crust Eggs).